The good food revolution : growing healthy food, people, and communities - Allen, Will, 1949- (Gotham Books, 2012)
Describes the author's early experiences as a sharecropper's son and a KFC executive before building a preeminent urban farm to feed, educate, and employ thousands of at-risk youths.